Development, in vitro and ex vivo characterization of lamotrigine-loaded bovine serum albumin nanoparticles using QbD approach - Maryana Salamah; Bence Sipos; Zsuzsanna Schelz; István Zupkó; Ágnes Kiricsi; Ágnes Szalenkó-Tőkés; László Rovó; Gábor Katona; György Tibor Balogh; Ildikó Csóka (Drug Delivery)
The present study aimed to prepare and optimize lamotrigine-loaded bovine serum albumin nanoparticles (LAM-NP) using the Quality by Design (QbD) approach and to investigate both the in vitro and ex vivo effects of different cross-linking agents glutaraldehyde (GLUT), glucose (GLUC) and 1-(3-dimethylaminutesopropyl)-3-ethylcarbodiimide hydrochloride (EDC) on intranasal applicability. Cross-linked LAM-NP from EDC (NP-EDC-1) showed the lowest Z-average value (163.7 ± 1.9 nm) and drug encapsulation efficacy (EE%) of 97.31 ± 0.17%. The drug release of GLUC cross-linked LAM-NP (NP-GLUC-9), glutaraldehyde cross-linked LAM-NP (NP-GLUT-2), and NP-EDC-1 at blood circulation conditions was higher than the initial LAM. The results of the blood-brain barrier parallel artificial membrane permeability assay (BBB-PAMPA) showed an increase in the permeability of LAM through the BBB with NP-GLUC-9 and an increase in flux with all selected formulations. The ex vivo study showed that LAM diffusion from the selected formulations through the human nasal mucosa was higher than in case of initial LAM. The cytotoxicity study indicated that BSA-NP reduced LAM toxicity, and GLUC 9 mM and EDC 1 mg could be alternative cross-linking agents to avoid GLUT 2% v/v toxicity. Furthermore, permeability through Caco-2 cells showed that nasal epithelial transport/absorption of LAM was improved by using BSA-NPs. The use of BSA-NP may be a promising approach to enhance the solubility, permeability through BBB and decrease the frequency of dosing and adverse effects of LAM.